KIT Mutation Associated with Depigmented Patches Regression and Multiple Café-au-lait Macules Development in a Patient with Piebaldism: A Case Report - Budair FM (Dove Medical Press, 2024)
Fatimah Mohammad Budair Department of Dermatology, King Fahd University Hospital, Al Khobar, College of Medicine, Imam Abdulrahman bin Faisal University, Dammam, Saudi ArabiaCorrespondence: Fatimah Mohammad Budair, Department of Dermatology, King Fahd University Hospital, Al Khobar, College of Medicine, Imam Abdulrahman bin Faisal University, Bashar Ibn Burd Street, Al Aqrabiyah 34445, Dammam, Saudi Arabia, Tel +00966503881480, Email fbudair@iau.edu.saAbstract: Piebaldism is a rare genetic disorder caused by KIT mutations and clinically characterized by fixed depigmented patches throughout the body. Herein, a case of piebaldism in which the depigmented patches regressed as the patient grew older, along with the development of multiple café-au-lait macules, is described. The likely pathogenic, heterozygous KIT c.1991-2A>G variant was detected as the potential cause of this unusual piebaldism phenotype. This case provides new knowledge on genotype-phenotype correlation of KIT mutations for piebaldism etiology and presentation.Keywords: genotype, phenotype, melanocyte, autosomal, rare disease